2005
DOI: 10.1002/chem.200401293
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of [NiCp*(2,5‐tBu2PC4H2)], a 20‐Valence‐Electron Phosphanickelocene

Abstract: The reaction of the bulky phospholide salt Li(2,5-tBu2PC4H2) x 2THF (1; THF = tetrahydrofuran) with [NiCp*(acac)] (HCp* = pentamethylcyclopentadiene, Hacac = acetylacetone) gives the green air-sensitive phosphanickelocene [NiCp*(2,5-tBu2PC4H2)] (2) in yields of about 85%. An X-ray structural determination of 2 shows long Ni-ring bonds and "delocalised" ring P-C and C-C bonds characteristic of a classical 20-valence-electron (ve) nickelocene. The electronic structure of 2 has been clarified through a combined A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 65 publications
(82 reference statements)
1
25
0
Order By: Relevance
“…[5,35] Additionally, few theoretical experiments on phospholyl complexes are present in the literature, [12,36] with landmark molecular orbital calculations on phosphaferrocenes probably being the most important.…”
Section: Resultsmentioning
confidence: 99%
“…[5,35] Additionally, few theoretical experiments on phospholyl complexes are present in the literature, [12,36] with landmark molecular orbital calculations on phosphaferrocenes probably being the most important.…”
Section: Resultsmentioning
confidence: 99%
“…The steric bulk of the SiMe 3 groups becomes apparent from the angles Fe-Ct1-Si (95.7°, 96.8°), which exceed the ideal value of 90°, while the deviation for the β-Me groups is significantly smaller (90.9°, 91.1°). In conclusion, the structural parameters of the parent compound differ only very slightly from those observed for the related phosphaferrocene and ruthenocene ([Cp*M{(2,5-tBu 2 )C 4 H 2 P}], M = Fe, [20] Ru [21] ) with tBu groups in place of the Me 3 Si groups. A closely related molecule with alkynyldimethylsilyl substituents was obtained by Mathey et 6 ].…”
Section: 5-bis(trimethylsilyl)-34-dimethylphosphaferrocene (6)mentioning
confidence: 71%
“…Probably owing to their high reactivity, anion radicals derived by reduction of five-membered heterocyclic aromatic systems have never been characterized structurally [7] before the present work. The deprotonated 1H-1,2,4-diazaphosphole group [3,5-R 2 dp] À (B) is a mixed nitrogen-phosphorus (s 2 l 3 ) analogue of Cp À and may be viewed as the combination of phospholyl [3,8] and pyrazolato (pz) [9] ions. Theoretical analyses and photoelectron spectra suggested that azaphospholes containing s 2 l 3 phosphorus atoms are highly aromatic.…”
Section: Sb]mentioning
confidence: 99%